Surfactant sorption & desorption on soil surfaces of varying clay content - Küçükaşık, M. Faruk. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2001., 2001)
In this research, sorption and desorption behavior of selected surfactants were investigated on a soil sample that was mixed with different clays at different ratios. The surfactants investigated were a cationic surfactant Benzethonium chloride (Hyamine 1622) and an anionic surfactant Sodium Dodecyl Sulphate (SDS). The clays were Kaolin, Attapulgite, and Calcium-Montmorillonite. The sorption and desorption isotherms of soils were fitted to the Langmuir and Freundlich isotherm equations, and related sorption and desorption constants were calculated from these isotherms. It was found that the sorption capacities for all of the three different types of clay at different mixing ratio for Hyamine were higher compared to those of SDS. On the other hand, desorption capacities for SDS is better than those of Hyamine.
Keywords: Surface active agents.; Soil absorption and adsorption.; Soil chemistry.